Pengaruh Jumlah Bagi Hasil Deposito, Likuiditas, dan Inflasi Terhadap Jumlah Deposito Mudharabah Pada Bank Syariah Mandiri Periode 2014-2018 - Nini Nini; Murniati Murniati; Rahmaita Rahmaita (Universitas Dharma Andalas, 2020)
ABSTRACT This research aims to determined an effect of deposit’s profit sharing partially towards mudharabah deposit amount, liquidity effect partially towards mudharabah deposit amount, inflation effect partially towards mudharabah deposit amount, an effect of deposit’s profit sharing, liquidity, and inflation on stimulant basis towards mudharabah deposit amount. This research is a qualitative research using secondary data type from 2014 until 2018 that obtained from linear regression analysis method using SPSS 21.documentation version. Based on hypothesis testing show that mudharabah deposit’s profit sharing and liquidity partially have significant effect towards mudharabah deposit amount since it’s own <0.05 significant value, while inflation have no significant effect towards mudharabah deposit amount. ABSTRAK Penelitian ini bertujuan untuk mengetahui Pengaruh Jumlah bagi hasil deposito secara parsial terhadap jumlah deposito mudharabah, pengaruh Likuiditas secara parsial terhadap jumlah deposito mudharabah, pengaruh Inflasi secara parsial terhadap jumlah deposito mudharabah, pengaruh Jumlah bagi hasil deposito, likuiditas, dan inflasi secara simultan terhadap jumlah deposito mudharabah. Penelitian ini termasuk penelitian kuantitatif yang menggunakan jenis data sekunder tahun 2014 sampai dengan 2018 diperoleh dari metode analisis linier regresi berganda dengan menggunakan program komputer SPSS versi 21